Signatures of clustering accessible with a Time Projection Chamber: TexAT - Bishop Jack; Ahn S.; Barbui M.; Kokalova Tz.; Koshchiy E.; Parker C.E.; Pirrie S.H.; Pollacco E.C.; Roeder B.T.; Rogachev G.V.; Saastamoinen A.; Wheldon C. (EPJ Web of Conferences)
Many experimental observables in clustering require high-sensitivity, almost background-free measurements. The use of Time Projection Chambers (TPCs) over the past 15 years have demonstrated their capability as a step change in the accessibility of many of these observables, as well as the possibility to study clustering via new techniques. A summary of the difficulties and pitfalls of determining the type of clustering from observables is briefly discussed, with a focus on α-condensation and the possibility of an additional (Efimov) 0+ state in 12C, below the Hoyle state. The expansion of the technique used to tackle this challenge to study 3α + p clustering in 13N is also discussed, highlighting the exciting opportunities TPCs provide to study clustering inaccessible by conventional means. Finally, an overview of the recent and upcoming advances in TPC technology is given as well as listing additional future challenges that are needed to be overcome, in the context of discussing the next-generation upgrade to the existing TexAT TPC, known as TeBAT (TExas Birmingham Active Target).